ZONAL FOREST COMMUNITIES AND FOREST ZONING OF WESTERN SIBERIA (RUSSIA) - Myasnikov, Al A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
Forests of Siberia are heterogeneous in species composition, productivity, types and nature of renewability. They are also heterogeneous in patterns of forest distribution on different categories of land, marshes, bare mountains, meadows and percentage of forest cover. This research investigates the main types of woody plants and geographical distribution of forest communities in Western Siberia. The forest zoning of Western Siberia was analyzed to reveal the features of zonal formation of forest biogeocenoses. Forest zoning and ecological and economic assessment of the productivity of forest communities within zones and regions make the basis for outlining the strategic priorities in the given territory, and help to develop a system of forestry and timber processing activities aimed to improve ecological and economic efficiency of forest resources.